Microwave Photonics Programs at DARPA - Ridgway, Richard W.; Dohrman, Carl L.; Conway, Joshua A. (Journal of lightwave technology, 2014)
Over the past ten years, DARPA has made significant investments toward advancing the field of microwave photonics. This paper reviews DARPA-funded progress in this subject over the past decade. DARPA-funded research has advanced the state-of-the-art for microwave-photonic components, including low noise laser diodes, electrooptic modulators and high power photodiodes, as well as microwave photonic link configurations, including photonic downconversion, reconfigurable optical filters and optical phase-locked loops. These investments have yielded dramatic improvements in spurious-free dynamic range (SFDR). Measured performance includes SFDRs exceeding 115 dB · Hz 2/3 at 16 GHz using broadband externally modulated links; exceeding 120 dB · Hz 2/3 at 10 GHz using sub-octave electrooptic modulators; near 135 dB · Hz 2/3 at 100 MHz using optical phased-locked loops as linear phase demodulators; and exceeding 125 dB · Hz 2/3 at 5 GHz using optical filtering, downconversion and predistortion compensation.